Identification and characterization of drought tolerant rice genotypes using physiological and biochemical traits - Awaji, Sushma M; Hanjagi, Prashantkumar S; Repudi, Shalem Raju; Suravi, Upaly Sushree; Baig, MJ; Swain, Padmini (ORYZA-An International Journal of Rice, 2022)
The present study was conducted to evaluate the performance of seven rice genotypes using morphological, physiological and biochemical parameters, under induced drought (water stress) conditions at seedling level using PEG6000 in Hoagland’s medium. At the end of the stress period sampling was done to record the root and shoot lengths and various physiological parameters viz., total chlorophyll content, cell membrane stability index (MSI), relative water content were estimated. Proline and Malondialdehyde (MDA) content were also estimated as biochemical parameters. The results obtained from the study revealed the existence of significant variation in the seven genotypes studied for different physiological and biochemical parameters. Out of the seven genotypes studied, HT-18 (AC-34973) had performed better than the tolerant check CR-143-2-2 and showed better root and shoot growth, maintained higher total chlorophyll content (2.6 mg/gm FW), relative water content (61.3%) and membrane stability index (MSI) (52.9%), it has also shown higher proline content (20.52 ?moles/gm FW) and lesser MDA content (0.068) under stress. To assess the membrane integrity under osmotic stress, roots from all the genotypes grown in hydroponic culture with 20% PEG were stained with Evan’s blue, where the stress effect is directly reflected on the intensity of Evans blue uptake by the cell. Because of more membrane damage, the roots of the susceptible genotype, IR-64, had taken up more stain than the roots of tolerant genotype HT-18. The present study has identified HT-18 as seedling level drought tolerant genotype.